“An umbrella full of holes?”: Corporate Restructuring, Redundancy and the Effectiveness of ICE Regulations - Taylor, Phil; Baldry, Chris; Danford, Andy; Stewart, Paul (Relations industrielles / Industrial Relations, 2009)
This article concerns the manner in which the European Union Information and Consultation of Employees (ICE) Directive has been implemented in the UK in the harsh corporate conditions of restructuring, redundancy and site closure. Drawing on interview and documentary evidence from six case companies (Peugeot-Citroën, General Motors, Prudential, Aviva, Marconi, Rolls-Royce), the article exposes major fault lines in the effectiveness of the UK’s ICE Regulations to provide even limited protection for employees who were presented with redundancy as a fait accompli. Contrary to management claims, ICE arrangements have not provided additional levels of representation either to complement unions or to fill the “representation gap” left by declining coverage. The failure to consult raises broader questions on the wider political and legislative environment in the UK.